Identification of potential liquefaction in Kabonena. Issue 1 (January 2021) - Badaruddin,; Abdullah,; Priambudi, M D; Rusli, M; Labania, H M D; Rugayya, S; Asrafil,
Abstract: The research was conducted in Kabonena village, which aims to see the subsurface structure and the liquefaction potential. The research was conducted using the geoelectric resistivity method with the Wenner system. The parameters used are geological data, hydrogeology and formation values to obtain between the resistivity value and the lithology of the study area. Furthermore, by considering the geological, hydrogeological conditions and formation factor values, the specific resistance values for each layer are interpreted. The results obtained show that the layers with specific resistance values of 39.16 - 97.9 Ωm are dominated by water-saturated sand/gravel. The resistivity value above 97.9 - 200 Ωm is the layer of molasses and alluvium deposits/coastal deposits, and the resistance value above 200 Ωm is the layer of crushed granite and granodiorite. The existence of a subsurface structure like this, so that in Kelurahan Kabonena it is called a liquefaction event. The location has a layer of saturated air that points to the east with a depth of less than 24 meters.